Kerjasama Komite Dan Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Madrasah Aliyah Negeri di Kota Banda Aceh - Mistaruddin, Mistaruddin (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Education plays a very important role in the process of improving the quality of human resources and is a process that is integrated with the process of improving the quality of human resources themselves. For this reason, the government implements School-Based Management which involves relevant stakeholders, especially the community. This study aims to find out and analyze the collaboration of the Committee (community) with the Head of Madrasa in terms of improving the quality of education at Madrasa Aliyah Negeri in Banda Aceh City. Data collection in this study was conducted by interview, documentation, and observation. While the results of this study are the authors find that the Cooperation Committee and the Head of MAN in Banda Aceh City have been carried out in the form of partnerships that synergize and mutually understand the roles and functions of each institution in order to improve the quality of Madrasah education, this is clearly seen by the implementation of the boarding school program, student creativity activities, extracurricular activities and also academic achievement of students who continue to increase along with the increasing intensity of collaboration of the committee and the head of the Madrasah as a whole in all aspects that include learning activities, facilities, infrastructure, and technical education materially and non materially, so that it gives a significant influence on the quality of education at Madrasah Aliyah Negeri in Banda Aceh City.